2020
DOI: 10.1055/a-1170-5004
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Obesity and Premenopausal Breast Cancer According to Intrinsic Subtypes – a Systematic Review

Abstract: Introduction Obesity is a well-established risk factor for postmenopausal hormone-receptor positive breast cancer. The relationship between premenopausal breast cancer intrinsic subtypes and obesity is not completely elucidated; therefore, this systematic review was conducted to give an overview about the existing evidence. Methods This review followed the PRISMA Statement for Systematic Reviews and Meta-analyses. Full electronic search was conducted in PubMed and Orbis for articles published in Engl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 42 publications
0
13
0
1
Order By: Relevance
“…Since specific morphologic and prognostic characteristics of young-onset breast cancer were advocated in previous findings [ 38 ], such as enhanced likelihood to be a large and poorly differentiated tumor, or less often containing hormone receptors at diagnosis, we further stratified the studies by age at breast cancer diagnosis, and found an increased risk of tumors without PR expression in young patients. High BMI (≥25 kg/m 2 ) was confirmed as another risk factor for developing breast cancer [ 85 ], and more specifically, obesity increases the risk for hormone receptor-positive breast cancer in postmenopausal women, but tends to increase the risk for TNBC in premenopausal women [ 86 ]. Evidence of the relation between BMI and Her2 status is limited [ 86 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since specific morphologic and prognostic characteristics of young-onset breast cancer were advocated in previous findings [ 38 ], such as enhanced likelihood to be a large and poorly differentiated tumor, or less often containing hormone receptors at diagnosis, we further stratified the studies by age at breast cancer diagnosis, and found an increased risk of tumors without PR expression in young patients. High BMI (≥25 kg/m 2 ) was confirmed as another risk factor for developing breast cancer [ 85 ], and more specifically, obesity increases the risk for hormone receptor-positive breast cancer in postmenopausal women, but tends to increase the risk for TNBC in premenopausal women [ 86 ]. Evidence of the relation between BMI and Her2 status is limited [ 86 ].…”
Section: Discussionmentioning
confidence: 99%
“…High BMI (≥25 kg/m 2 ) was confirmed as another risk factor for developing breast cancer [ 85 ], and more specifically, obesity increases the risk for hormone receptor-positive breast cancer in postmenopausal women, but tends to increase the risk for TNBC in premenopausal women [ 86 ]. Evidence of the relation between BMI and Her2 status is limited [ 86 ]. Here, stratified analyses found a positive association between T2DM and lack of Her2 expression in studies [ 42 , 43 ] with BMI adjustment; these two studies had small sample sizes and recruited younger participants.…”
Section: Discussionmentioning
confidence: 99%
“…Außerdem scheint es weitere metabolische Faktoren zu geben, die unabhängig vom BMI einen Einfluss auf das Brustkrebsrisiko haben 43 . Auch hinsichtlich der Prognose konnte gezeigt werden, dass Übergewicht einen negativen Einfluss auf den Krankheitsverlauf und den molekularen Subtyp hat 46 , 47 . Dies lässt vermuten, dass eine Verbindung von Metabolismus und Brustkrebsrisiko mit komplexeren Mechanismen existiert.…”
Section: Einfluss Von Ernährung Und Mikrobiom Auf Das Brustkrebsrisikounclassified
“…Moreover, there seem to be other metabolic factors affecting the risk of breast cancer independently of BMI [43]. With regard to prognosis, it has also been established that obesity has a negative effect on the course of the disease and the molecular subtype [46,47] This suggests a link between metabolism and breast cancer risk with more complex mechanisms. One study looking into this is the cohort study "NutriNet-Santé" [48].…”
Section: Impact Of Diet and Microbiome On Breast Cancer Riskmentioning
confidence: 99%
“… 4 , 5 Increased body mass index (BMI) in premenopausal women shows a higher proportion of hormone receptor negative, with a predominance of triple negative breast cancer (TNBC) molecular subtype. 6 , 7 …”
Section: Introductionmentioning
confidence: 99%